Hydrodynamics and Musculature Actuation of Fish during a Fast Start - Yuhan Li; Jialei Song; Ling Yin; Bowen Jin; Bo Yin; Yong Zhong (Applied Sciences, 2023)
The fast start of fish is a rapid event that involves fast actuation in musculature and highly unsteady hydrodynamics. Fast-start capability is of great significance for fish to either hunt prey or escape from predators. In this study, we used a three-dimensional CFD model to study the hydrodynamics of a crucian carp during a C-type fast start. This study confirms the previous observations from both experiments and simulations that the jets are induced by the fast start for force generation, and the vortex rings generated in both the preparation and propulsion stages connect to each other. In addition, an obvious vortex ring generated by the head during the propulsion stage was observed, which potentially benefits the rotational motion during the fast start. According to the hydrodynamic information from CFD modeling, we established a model to analyze the internal torque, which represents the muscular actuation. The backward traveling speed of internal torque is 1.56 times the curvature speed, which confirms the existence of neuromechanical phase lag during the fast start of fish. This study potentially benefits the design of robot fish in terms of kinematics and driving mode.